Auxin Metabolite Profiling in Isolated and Intact Plant Nuclei - Skalický, Vladimír; Vojtková, Tereza; Pěnčík, Aleš; Vrána, Jan; Juzoń, Katarzyna; Koláčková, Veronika; Sedlářová, Michaela; Kubeš, Martin F; Novák, Ondřej (International journal of molecular sciences, 2021)
The plant nucleus plays an irreplaceable role in cellular control and regulation by auxin (indole-3-acetic acid, IAA) mainly because canonical auxin signaling takes place here. Auxin can enter the nucleus from either the endoplasmic reticulum or cytosol. Therefore, new information about the auxin metabolome (auxinome) in the nucleus can illuminate our understanding of subcellular auxin homeostasis. Different methods of nuclear isolation from various plant tissues have been described previously, but information about auxin metabolite levels in nuclei is still fragmented and insufficient. Herein, we tested several published nucleus isolation protocols based on differential centrifugation or flow cytometry. The optimized sorting protocol leading to promising yield, intactness, and purity was then combined with an ultra-sensitive mass spectrometry analysis. Using this approach, we can present the first complex report on the auxinome of isolated nuclei from cell cultures of Arabidopsis and tobacco. Moreover, our results show dynamic changes in auxin homeostasis at the intranuclear level after treatment of protoplasts with free IAA, or indole as a precursor of auxin biosynthesis. Finally, we can conclude that the methodological procedure combining flow cytometry and mass spectrometry offers new horizons for the study of auxin homeostasis at the subcellular level.
Keywords: homeostáza; frakcionace buněk; flow cytometry; auxin metabolism; Cell Nucleus; centrifugace; Arabidopsis; indoly; regulátory růstu rostlin; Homeostasis; buněčné kultury; kyseliny indoloctové; buněčné jádro; Mass Spectrometry; Protoplasts; Flow Cytometry; auxin; Centrifugation; rostlinné buňky; průtoková cytometrie; Nicotiana; protoplasty; Indoleacetic Acids; Plant Growth Regulators; Indoles; Cell Culture Techniques; Plant Cells; Cell Fractionation; subcellular fractionation; hmotnostní spektrometrie; nucleus; tabák